การพัฒนารูปแบบการเรียนการสอนที่เน้นการเห็นความสำคัญของการเรียนรู้ และการเรียนรู้แบบลึกเพื่อเสริมสร้างความสามารถในการอ่านภาษาอังกฤษเพื่อความเข้าใจของนักเรียนระดับประถมศึกษา - ผัสสพรรณ ถนอมพงษ์ชาติ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purposes of this research are: 1) to develop a reading instructional model based on the concepts of significant learning approach and deep learning approach to enhance English reading comprehension ability of primary school students; and 2) to evaluate the quality of the developed instructional model.The research procedure was divided into 3 phases. The first phase was to develop a reading instructional model based on the concepts of significant learning approach and deep learning approach. The second phase was to construct the research instruments. The third phase was to evaluate the quality of the developed instructional model by implementing with 29 fifth grade students at Chulalongkorn University Elementary Demonstration School. The samples were purposively selected from fifth grade students. The research instruments were the reading comprehension test and the student’s changing behavior interview. The duration of experiment was 5 weeks (16 hours, 7 lesson plans). The data were analyzed using t-test. The findings of this study were as follows:1. The developed reading instructional model based on the concepts of significant learning approach and deep learning approach has 6 steps: (1) Engaging the students (2) Learning new vocabulary (3) Reading aloud (4) Completing reading exercise and feedback (5) Activating vocabulary and (6) Individual reading and assessment 2. The quality of the developed reading instructional model was investigated by implementing the model in the class. After studying through the developed reading instructional model, the post-test mean scores of students’ English reading comprehension ability were higher than their pre-test mean scores at the statistically significance at .05 level.